THE PREVALENCE OF HYPERTENSION AMONG YOUNG ADULT PATIENTS AT KLINIK SOEDIRMAN PURWOKERTO - Sinensis, Rizki Amelia; Wicaksono, Madya Ardi; Nafiisah, Nafiisah; Firinda, Rizma Haidif; Kamal, Isran (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Hypertension is a growing public health problem, particularly among young adults. This study aims to determine the prevalence of hypertension among young adult patients at Klinik Soedirman Purwokerto. The study uses a quantitative descriptive design with a sample of all patients aged 18-24 years who accessed healthcare services at the clinic from March to September 2024. The results show that the majority of patients were female (72.51%), with the most frequent age group being 20 years (29.75%). Recorded diagnoses of hypertension included both essential and secondary hypertension, with one case of both types found in a 20-year-old female patient. Risk factors contributing to hypertension in young adults include unhealthy lifestyle factors such as high salt diet, lack of physical activity, alcohol consumption, and smoking habits. These findings indicate the need for more effective preventive programs among young adults, such as promoting healthy lifestyles and routine blood pressure screening. This study can serve as a basis for designing hypertension prevention measures among students, particularly at Jenderal Soedirman University